2014
DOI: 10.1186/s40781-014-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 1α, 25-dihydroxyvitamin D3 [1, 25(OH)2D3] on the expression of Sox 9 and the transient receptor potential vanilloid 5/6 ion channels in equine articular chondrocytes

Abstract: BackgroundSox 9 is a major marker of chondrocyte differentiation. When chondrocytes are cultured in vitro they progressively de-differentiate and this is associated with a decline in Sox 9 expression. The active form of vitamin D, 1, 25 (OH)2D3 has been shown to be protective of cartilage in both humans and animals. In this study equine articular chondrocytes were grown in culture and the effects of 1, 25 (OH)2D3 upon Sox 9 expression examined. The expression of the transient receptor potential vanilloid (TRPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…On the other hand, further evaluation is required to test if vitamin D metabolites cause OA. One in vitro study indicates the active vitamin D metabolite, 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), activates matrix metallopeptidase 13 expression, which plays a major role in cartilage degradation 19 , while another reported that 1,25(OH) 2 D 3 suppresses OA by increasing the expression of Sox 9, a marker of chondrocyte differentiation 20 . In addition, the joint may be affected by vitamin D metabolites of non-canonical pathways 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, further evaluation is required to test if vitamin D metabolites cause OA. One in vitro study indicates the active vitamin D metabolite, 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), activates matrix metallopeptidase 13 expression, which plays a major role in cartilage degradation 19 , while another reported that 1,25(OH) 2 D 3 suppresses OA by increasing the expression of Sox 9, a marker of chondrocyte differentiation 20 . In addition, the joint may be affected by vitamin D metabolites of non-canonical pathways 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a series of gene expression that benefits OA treatment occurs . For instance, calcitriol can upregulate the expression of SOX9 and collagen II (Col2) and effectively downregulate the expression of matrix metalloproteinases (MMP)-9 and MMP-13 . Hence, calcitriol is deemed as an emerging and potential disease-modifying OA drug (DMOAD) that can elicit positive responses to inhibit OA progression .…”
Section: Introductionmentioning
confidence: 99%